2015
DOI: 10.1007/s11517-015-1369-5
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted liver tumor surgery using a novel semiautomatic and a hybrid semiautomatic segmentation algorithm

Abstract: We developed a medical image segmentation and preoperative planning application which implements a semiautomatic and a hybrid semiautomatic liver segmentation algorithm. The aim of this study was to evaluate the feasibility of computer-assisted liver tumor surgery using these algorithms which are based on thresholding by pixel intensity value from initial seed points. A random sample of 12 patients undergoing elective high-risk hepatectomies at our institution was prospectively selected to undergo computer-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Many different approaches have been proposed to improve the tumor segmentation performance. Recent publications mainly included semiautomatic and automatic tumor segmentation methods based on region growing or thresholding [ 6 8 ], clustering [ 9 11 ], level set [ 12 , 13 ], graph cuts [ 14 , 15 ], and machine learning [ 16 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many different approaches have been proposed to improve the tumor segmentation performance. Recent publications mainly included semiautomatic and automatic tumor segmentation methods based on region growing or thresholding [ 6 8 ], clustering [ 9 11 ], level set [ 12 , 13 ], graph cuts [ 14 , 15 ], and machine learning [ 16 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern software solutions and systems have been developed that allow manual, automatic or semiautomatic segmentation of medical liver images with acceptable results[16,20-22]. Our team developed the PROMETHEIA system which uses a hybrid semiautomatic segmentation method that allow of a rapid and easy segmentation that can be performed even by a surgeon[7,23]. The patient-specific 3D models produced using our algorithms proved to be accurate and effectively enhanced the intraoperative medical image guidance.…”
Section: D Modelsmentioning
confidence: 99%
“…Since most of the intraoperative discovered liver tumours have a diameter of less than 1.5 cm, they can be incorporated manually in 3D liver models as simple spheres. We have implemented this approach in our computer analysis system for liver surgery and test it in clinical practice[18,23]. Our results showed that the incorporation of newly found tumours was possible, safe and accurate and the intraoperative plan had to be changed in 21% of the cases.…”
Section: Intraoperative Risk-analysismentioning
confidence: 99%
“…In this eld, surface representation and tessellation 3 [51] are the predominant uses for Bézier surfaces.…”
Section: High-performance Computing Of Bézier Surfacesmentioning
confidence: 99%
“…To be sure, the major bottleneck is segmentation (currently is subject to extensive research), which automation is still considered as a challenging task [51], thus requiring some degree of human interaction. While segmentation falls out of the scope of this work, the integration ability of PSR and how this can increase the adoption of 3D patient-speci c models with the help of state-of-the-art tools, like MeVis Distant Services [51,52,53] or Fuji lm Synapse VINCENT [54], is a relevant question. PSR can be seamlessly integrated in any medical platform, provided that the platform is able to obtain segmented images (Figure 6.1).…”
Section: Integration Of Psr In Clinical Workflowsmentioning
confidence: 99%